KADAR HEMOGLOBIN, LEUKOSIT DAN TROMBOSIT PENDERITA MALARIA TROPIKA +3 DAN +4 DI RSUD KWAINGGA KABUPATEN KEEROM PAPUA - Herlando Sinaga; Ester Rampa; Tika Romadhonni; Jannete Elisabeth Taroreh; Yusuf Pare (LP2M IIK (Lembaga Penelitian dan Pengabdian Masyarakat Institut Ilmu Kesehatan) Bhakti Wiy, 2023)
Background: Malaria is still a public health problem that can cause death, especially in high-risk groups, namely infants, toddlers and pregnant women. The purpose of this study was to determine the levels of hemoglobin, leukocytes and platelets in patients with tropical malaria +3 and +4. Research Objectives: This study aims to determine the levels of Hemoglobin, Leukocytes and Platelets. Blood tests of patients with tropical malaria are +3 and +4. Research Methods: The type of research that will be used is descriptive research method with a sample of 36 patients. To determine the levels of hemoglobin, leukocytes and platelets, blood examination of patients with tropical malaria +3 and +4 was performed using a microscope and a 5010 photometer. The results obtained from this study were tabulated and analyzed descriptively. Research Results: Based on the research, it was shown that from 21 patients with +3 tropical malaria, 11 (52%), normal hemoglobin levels were found in 10 (52%), low hemoglobin levels in 10 (48%); Normal leukocytes were 15 (71%), low leukocytes were 2 (10%) and high was 4 (19%). As for the normal platelet results as many as 9 (43%) and low as many as 12 (57%). For the results of the study, 15 patients with tropical malaria +4 obtained normal hemoglobin levels of 6 (40%) and low of 9 (60%); 10 normal leukocytes (67%), low leukocytes 3 (20%) and high leukocytes 2 (13%). As for the normal platelet results as many as 4 (27%) and 11 (73%). Conclusion: These results indicate that +3 Tropical malaria patients experienced the most decrease in platelets as much as 57% and +4 Tropical Malaria patients experienced a 60% decrease in hemoglobin and 73% low platelets.